2005
DOI: 10.1364/ol.30.000558
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced phase transition in VO_2 nanocrystals: ultrafast control of surface-plasmon resonance

Abstract: We study the ultrafast insulator-to-metal transition in nanoparticles of VO2, obtained by ion implantation and self-assembly in silica. The nonmagnetic, strongly correlated compound VO2 undergoes a reversible phase transition, which can be photoinduced on an ultrafast time scale. In the nanoparticles, prompt formation of the metallic state results in the appearance of surface-plasmon resonance. We achieve large, ultrafast enhancement of optical absorption in the near-infrared spectral region that encompasses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
119
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(129 citation statements)
references
References 11 publications
1
119
0
Order By: Relevance
“…131 The photo-generation of holes in the valence band, induced by a near-infrared laser pulse, triggers a phase transition into a conductive state and the appearance of a LSPR. 127,132 Since this process is non-thermally activated, it is very fast and the switching speed is generally limited by the temporal width of the laser pulse. However, the reverse transition to the insulator state is a thermal process and it is much slower (in the range of nanoseconds) because it is limited by how fast heat can diffuse out of the NC sample.…”
Section: Transition Metal Dioxidesmentioning
confidence: 99%
See 2 more Smart Citations
“…131 The photo-generation of holes in the valence band, induced by a near-infrared laser pulse, triggers a phase transition into a conductive state and the appearance of a LSPR. 127,132 Since this process is non-thermally activated, it is very fast and the switching speed is generally limited by the temporal width of the laser pulse. However, the reverse transition to the insulator state is a thermal process and it is much slower (in the range of nanoseconds) because it is limited by how fast heat can diffuse out of the NC sample.…”
Section: Transition Metal Dioxidesmentioning
confidence: 99%
“…However, the reverse transition to the insulator state is a thermal process and it is much slower (in the range of nanoseconds) because it is limited by how fast heat can diffuse out of the NC sample. 127 In one of the few studies published so far on VO 2 NCs, Rini et al reported a pump-probe investigation on VO 2 NCs and nanorods grown by ion implantation and self-assembly in silica. 127 Much work has gone into doping ''traditional'' semiconductor materials (group IV and III-V semiconductors) in order to obtain the high density of free carriers necessary to make them plasmonic.…”
Section: Transition Metal Dioxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Representative TEM pictures of the corresponding samples are shown at the right. After [88] theory predicts absorption features at longer wavelengths for polarization parallel to the major axis. Therefore, the continuous angular distribution of randomly oriented rods in the ion-implanted samples results in an overall broadening of the absorption spectrum toward longer wavelengths.…”
Section: Smart Nanocompositesmentioning
confidence: 99%
“…Furthermore, the phase transition can be induced by infrared light pulses of less than 200 fs duration [88]. Indeed, the phase transition can be optically triggered by electronic excitation on a timescale sorter than that of a thermal path.…”
Section: Smart Nanocompositesmentioning
confidence: 99%